2016
DOI: 10.1128/aac.02328-15
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Synthetic and Natural Host Defense Peptides with Leishmanicidal Activity

Abstract: Leishmania parasites are a major public health problem worldwide. Effective treatment of leishmaniasis is hampered by the high incidence of adverse effects to traditional drug therapy and the emergence of resistance to current therapeutics. A vaccine is currently not available. Host defense peptides have been investigated as novel therapeutic agents against a wide range of pathogens. Here we demonstrate that the antimicrobial peptide LL-37 and the three synthetic peptides E6, L-1018, and RI-1018 exhibit leishm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…The low GC content of these three genes could explain their absence from identification in the output pool, as the mini-Tn 5 transposon used to create the PA45B mutant library preferentially inserts into GC-rich regions ( 42 ). This has also been observed in another TraDIS study using the mini-Tn 5 transposon, where an overall increased transposon insertion frequency in high-GC versus low-GC regions was observed ( 43 ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The low GC content of these three genes could explain their absence from identification in the output pool, as the mini-Tn 5 transposon used to create the PA45B mutant library preferentially inserts into GC-rich regions ( 42 ). This has also been observed in another TraDIS study using the mini-Tn 5 transposon, where an overall increased transposon insertion frequency in high-GC versus low-GC regions was observed ( 43 ).…”
Section: Discussionsupporting
confidence: 74%
“…PA45B was sequenced on a Pacific Biosciences (PacBio) 249 RSII system using the P4 polymerase and C2 sequencing chemistry. The raw sequencing data were assembled as previously described ( 43 ). Annotation of the PA45B genome sequence was performed using PROKKA v1.11 ( 63 ) and the EcoCyc database ( 64 ), and the sequence was visualized in Artemis ( 65 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, sunbathing is recommended for patients with tuberculosis, in order to favour the production of LL-37 and consequently the kill of M. tuberculosis (Rivas-Santiago et al ., 2008). In addition, the LL-37 peptide has been shown to have antileishmanial activity against promastigotes and amastigotes of L. donovani and L. major (Marr et al ., 2016). It also has been shown that cathelicidins interact with membranes of pathogens causing permeation and disintegration of these cell membranes (Kościuczuk et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In order to combat the resistant strains, various combinatorial therapies have been used. Due to increased drug selectivity, reduced toxicity and compatibility with the target protein structures AMPs, for example, dermaseptins, cecropins, melettin, etc., have been described as a first line of defense against pathogen invasion, including protozoa (Hopkins and Groom, 2002;Lynn et al, 2011;Mangoni et al, 2005;Marr et al, 2016;Toro et al, 2013;Ruiz-Santaquiteria et al, 2017) and are under intense investigation to improve their druggability. Their mode of action involves the perturbation of protozoan homeostasis by directly disrupting the cellular membranes, interaction and interference with key processes in the parasite metabolism (Afacan et al, 2012;Jenssen et al, 2006;Torrent et al, 2012b).…”
Section: Antiparasiticmentioning
confidence: 99%